2014
DOI: 10.1182/blood-2014-05-574830
|View full text |Cite
|
Sign up to set email alerts
|

PKC-β as a therapeutic target in CLL: PKC inhibitor AEB071 demonstrates preclinical activity in CLL

Abstract: Key Points• AEB071 demonstrates preclinical in vitro and in vivo activity against CLL independent of survival signaling and stromal cell protection.• AEB071 can either inhibit or activate the WNT pathway emphasizing the importance of pharmacodynamic monitoring in its development.Targeting B-cell receptor (BCR) signaling in chronic lymphocytic leukemia (CLL) has been successful with durable remissions observed with several targeted therapeutics. Protein kinase C-b (PKC-b) is immediately downstream of BCR and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…In multiple myeloma, pharmacologic inhibition of activated PKCbII using enzastaurin inhibited growth factors and cytokines secreted by multiple myeloma-derived bone marrow stromal cells (28). In CLL, PKCb is immediately downstream of the B-cell receptor and has been shown to be important to CLL cell autocrine survival and proliferation in vivo (43). PKCb is also essential for the development of CLL in the TCL1 transgenic mouse model, making it a valid therapeutic target in this malignancy (44).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple myeloma, pharmacologic inhibition of activated PKCbII using enzastaurin inhibited growth factors and cytokines secreted by multiple myeloma-derived bone marrow stromal cells (28). In CLL, PKCb is immediately downstream of the B-cell receptor and has been shown to be important to CLL cell autocrine survival and proliferation in vivo (43). PKCb is also essential for the development of CLL in the TCL1 transgenic mouse model, making it a valid therapeutic target in this malignancy (44).…”
Section: Discussionmentioning
confidence: 99%
“…49 In support of this, AEB071 is currently being studied in a phase II clinical trial in diffuse large B-cell lymphoma, and has recently been demonstrated to have pre-clinical activity in CLL in vitro and in vivo. 50 Targeting PKC, and in particular PKCb, is especially pertinent given the recent findings of Lutzny et al, who demonstrated that PKCbII expression in bone marrow stromal cells is essential for the survival and development of CLL cells. 51 Therefore, inhibition of PKCb may modify the tumor microenvironment, which has been established to play a critical role in supporting CLL survival, proliferation and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…For those with PCLG2 mutations or BTK mutations, other downstream targets such as PKCb might also be clinically relevant. Preclinical testing with sotrastaurin has shown proof of concept in this area 35 ; however, clinical studies are not being pursued in this population with this particular agent.…”
Section: Other Promising Drugs and Targetsmentioning
confidence: 99%